Case report of Nasopharyngeal Angiofibroma in a teenager female, a rare finding - Sundas Masood, Nausheen Qureshi, Fatima Shahid, Memoona Afzal, Aeimen Fatima, Asmara Hussain (Journal of Rawalpindi Medical College, 2021)
Background: Angiofibroma is a rare histologically benign tumor that is an unencapsulated, highly vascular tumor.1 It shows very aggressive behavior due to local invasiveness and is associated with various symptoms.2 Angiofibroma is almost always seen in young adolescent males.2 Along main pathogenesis is unknown, but it is considered to be associated with sex hormones mainly testosterone and estradiol.3 In a study conducted from 1995 to 2012 all patients were male.4 Major symptoms include nasal obstruction and epistaxis and surgical removal of the tumor as a whole is considered the treatment of choice.5 There have been very few individual case reports of angiofibroma in females 6-9 which were confirmed with radiological testing and histopathology report of the samples taken. Case presentation: We present a rare case of nasopharyngeal angiofibroma in a young female as confirmed by computed tomography scan findings and histopathology reports of the sample by well-qualified pathologists. Conclusion: The case is being reported to increase awareness among medical professionals and encouraging further workup on the pathogenesis of angiofibroma.